Social anxiety and self efficacy as predictors of social media addiction in adolescents - Kaygas, Yasemin; Şam, Mehmet; Doğan, Yıldız Burcu; Yalçın, Ceyda; Sonkur, Ali; Eker Durmuş, Esra (Journal of Dependence, 2023)
Objective: The aim of the current study was to determine the effects of social anxiety, academic self-efficacy, social self-efficacy, emotional self-efficacy on predicting adolescents’ social media addiction. Method: The study group of this research consisted of 532 students continuing their education in the 7th and 8th grades. While determining the study group of the research, easily accessible case sampling, one of the sampling methods, was used. The relational survey method was administered in this study. "Social Media Addiction Scale for Adolescents", the "Social Anxiety Scale for Adolescents", the "Self-Efficacy Scale for Children" and the "Personal Information Form" were used as data collection instruments. Results: The results of the study show that there is a positive significant relationship between social media addiction and social anxiety and a negative significant relationship between social media addiction and academic self-efficacy, social self-efficacy, and emotional self-efficacy. According to the results of the multiple regression analysis, it was concluded that adolescents’ social anxiety, academic self-efficacy and social self-efficacy scores were a significant predictor of social media addiction, but emotional self-efficacy scores were not a significant predictor of social media addiction. Conclusion: The findings obtained as a result of the research were weighed in the context of other research findings, and suggestions were made to the practitioners and researchers.